2023
DOI: 10.1111/1751-2980.13175
|View full text |Cite
|
Sign up to set email alerts
|

Alterations and clinical relevance of gut microbiota in patients with Peutz–Jeghers syndrome: A prospective study

Abstract: Objective In this case–control study we aimed to investigate the intestinal microbiota profile of patients with Peutz‐Jeghers syndrome (PJS) and its association with polyp growth. Methods Thirty‐two PJS patients and 35 healthy controls were enrolled. Fecal samples of all participants were collected for gut microbiota analysis via 16S rRNA gene (regions V3–V4) sequencing. SPSS version 22.0 and R software version 3.1.0 were used for the statistical analysis. Results The richness was comparable, while the overall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…Consistent with our results, Wang et al indicated that genus Bacteroides were enriched, while the genus Blautia were decreased in patients with PJS. Besides, Du et al investigated the feature of gut microbiota in 32 PJS patients and analyzed the relationship between gut microbiota and the growth of polyps [ 31 ]. The results suggested that the structure of the gut microbiota differed between healthy controls and PJS patients, while the richness was comparable.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with our results, Wang et al indicated that genus Bacteroides were enriched, while the genus Blautia were decreased in patients with PJS. Besides, Du et al investigated the feature of gut microbiota in 32 PJS patients and analyzed the relationship between gut microbiota and the growth of polyps [ 31 ]. The results suggested that the structure of the gut microbiota differed between healthy controls and PJS patients, while the richness was comparable.…”
Section: Discussionmentioning
confidence: 99%